MODEL-BASED BUDGET PERFORMANCE KOLAKA DISTRICT EAST SOUTHEAST SULAWESI PROVINCE - Dervish, Mustakim; Rahmat, H.; Arsyad, Armin; Yunus, H. Muhammad (IJRDO - Journal of Applied Management Science, 2015)
This study aimed to analyze the budgeting process and find the model of performance-based budgeting (Performance budgetting) For the necessary information and empirical data on the phenomenon (phenomenon). The phenomenon in question is the relationship between input, output, efficiency, quality and results (Outcome) on budget revenue and expenditure Kolaka East with qualitative patterns. Model Performance-based budgeting starts from preparation and accountability of the budget include : Process Planning, Budgeting, Determination of the budget, Translation of the budget set and accountability of the budget. The budget process-based performance is influenced by the role of the legislature in budget formulation which includes : a role in the cycle of budget planning and The budget cycle revenue and expenditure Kolaka East